Effects of therapeutic angiogenesis with plasmid VEGF165 on ventricular function in a canine model of chronic myocardial infarction - Furlani,Ana Paula (2009)
OBJECTIVE: Therapeutic angiogenesis is currently under investigation in ischemic heart disease. We examined the effect on left ventricular function induced by therapeutic angiogenesis by intramyocardial injection of plasmid VEGF165, in a canine model of chronic myocardial infarction. METHODS: Left thoracotomy was performed in 10 mongrel dogs, and myocardial infarction induced by ligation of the major diagonal coronary artery. At 7 postoperative (p.o.) day (pre-treatment), left ventricular ejection fraction was assessed by echocardiogram, and a second procedure was done: saline or plasmid VEGF165 at 200 mg/mL was injected over 10 points of the ischemic areas of control or treated groups, respectively. Fourteen days later (post-treatment, day 21) a control echocardiogram was performed, the animals were sacrificed and histological examination was performed. RESULTS: Ejection fraction was maintained in the treated group: 52.45 + 15.1% on day 7 and 48.53 + 11.74% on day 21 (P=0.59), and tended to decrease in the control group, from 59.3 + 4% to 39.37 + 19.43% (P=0.04), although absolute values did not differ significantly between groups. Histological examination revealed a non significant increase in capillary vessels number in all areas in treated group. Paradoxically, arterioles were significantly less in number in all areas of treated dogs. CONCLUSION: Intramyocardial injection of plasmid VEGF165, in this canine model of chronic myocardial infarction, resulted in preservation of left ventricular ejection fraction, contrary to the control group where left ventricular ejection fraction showed continuous decline during the experiment. Histological examination, however, was unable to explain completely these results.